From Linkage Studies to Epigenetics: What We Know and What We Need to Know in the Neurobiology of Schizophrenia - Cariaga-Martinez, Ariel; Saiz-Ruiz, Jerónimo; Alelú-Paz, Raúl (Frontiers in Neuroscience, 2016)
Schizophrenia is a complex psychiatric disorder characterized by the presence of positive, negative and cognitive symptoms that lacks a unifying neuropathology. In the present paper, we will review the current understanding of molecular dysregulation in schizophrenia, including genetic and epigenetic studies. In relation to the latter, basic research suggests that normal cognition is regulated by epigenetic mechanisms and its dysfunction occurs upon epigenetic misregulation, providing new insights into missing heritability of complex psychiatric diseases, referring to the discrepancy between epidemiological heritability and the proportion of phenotypic variation explained by DNA sequence difference. In schizophrenia the absence of consistently replicated genetic effects together with evidence for lasting changes in gene expression after environmental exposures suggest a role of epigenetic mechanisms. In this review we will focus on epigenetic modifications as a key mechanism through which environmental factors interact with individual's genetic constitution to affect risk of psychotic conditions throughout life.